The effect of reinforcing with natural fibers on the mechanical properties of unsaturated polyester composites (Damascus University Journal for engineering sciences, 2023)
Natural fibers are diverse and their sources are renewed annually of all kinds, they have good adhesion strength with polymers ,in addition to the low cost of obtaining and processing them compared to synthetic fibers.This research aims to study the effect of reinforcing with natural fibers (hemp tissue, date palm mat, luffa cylindrica) on mechanical properties (tensile strength and bending) of unsaturated polyester (UPR) composites. The tensile test results showed an improvement in tensile stress values by increasing the number of reinforcing fibers layers, and hemp tissue gave the best values, followed by luffa cylindrica and date palm mat.By testing the samples on bending, it was revealed that the best results are for the composites reinforced with luffa cylindrica, followed by hemp tissue and then date palm mat. The results also showed that dealing with date palm in reinforcing UPR requires treatment system that goes beyond chemical treatment with sodium hydroxide.
Keywords: natural fibers; hemp tissue; date palm; luffa cylindrica; reinforced composites